Magnesium and Vitamin D Supplementation on Exercise Performance. Issue 4 (8th October 2021) - Hunt, Giavanna; Sukumar, Deeptha; Volpe, Stella L.
ABSTRACT: Magnesium and vitamin D are two micronutrients that contribute directly to the metabolism of macronutrients, maintenance of muscle function, and various metabolic processes (i.e., protein synthesis and bone metabolism). Dietary recommendations are established based on age and gender differences; however, energy expenditure is not accounted for in determining these values. It is believed that athletes may require greater nutrient quantities than less active populations because of their increased energy expenditure. Nutrient intake values have yet to be determined for athletes, leading to inadequate energy intake, deficiencies, and insufficiencies; thus, supplementation may be an effective way of achieving nutrient adequacy in athletes. The purpose of this narrative review was to present research pertaining to magnesium supplementation and vitamin D supplementation on exercise performance. A systematic keyword search for articles from PubMed was conducted from June to August 2020. The search terms included various words related to the topic. Inclusion criteria required articles to be available in English; to be a clinical trial, randomized controlled trial, or longitudinal study; and to involve magnesium supplementation, vitamin D supplementation, or supplementation of both micronutrients. In addition, the research conducted on magnesium or vitamin D were required to focus on athletes or those who exercised regularly. However, because of the paucity of published data regarding the combined effects of magnesium and vitamin D supplementation on exercise performance, those studies that could provide some information in nonathletic populations were included. The search did not limit the years in which studies were published because of the scarcity of articles related to the topic. After reviewing the articles for originality and applicability, 13 studies were included in our narrative review. Some researchers have reported that magnesium supplementation may provide ergogenic benefits via contributions to muscle function and recovery. In addition, some researchers have reported that vitamin D supplementation may positively affect physical endurance and muscle recovery in athletes. However, more research is required to provide more definitive conclusions. The interactions between magnesium and vitamin D during metabolism may potentiate the functions of each micronutrient, making the combined effects of magnesium and vitamin D greater than the effects of either one alone. However, research is required to elucidate their combined effects on exercise performance.